BrUFO positively regulates the infection of Chinese cabbage by Plasmodiophora brassicae - Zhang, Bo; Feng, Hui; Ge, Wenjie; Wang, Xinlei; Zhang, Jing; Ji, Ruiqin (Frontiers in Plant Science, 2023)
Introduction Chinese cabbage is one of the most important vegetable crops in China. However, the clubroot disease caused by the infection of Plasmodiophora brassicae (P. brassicae) has seriously affected the yield and quality of Chinese cabbage. In our previous study, BrUFO gene was found to be significantly up-regulated in diseased roots of Chinese cabbage after inoculation with P. brassicae. UFO (UNUSUAL FLORAL ORGANS) have the properties of substrate recognition during ubiquitin-mediated proteolysis. A variety of plant can activate immunity response through the ubiquitination pathway. Therefore, it is very important to study the function of UFO in response to P. brassicae. Methods In this study, The expression pattern of BrUFO Gene was measured by qRT-PCR and In situ Hybridization (ISH). The expression location of BrUFO in cells was determined by subcellular localization. The function of BrUFO was verified by Virus-induced Gene Silencing (VIGS). proteins interacting with BrUFO protein were screened by yeast two-hybrid. Results Quantitative real-time polymerase chain reactions (qRT-PCR) and in situ hybridization analysis showed that expression of BrUFO gene in the resistant plants was lower than that in susceptible plants. Subcellular localization analysis showed that BrUFO gene was expressed in the nucleus. Virus-induced gene silencing (VIGS) analysis showed that silencing of BrUFO gene reduced the incidence of clubroot disease. Six proteins interacting with BrUFO protein were screened by Y2H assay. Two of them (Bra038955, a B-cell receptor-associated 31-like protein and Bra021273, a GDSL-motif esterase/acyltransferase/lipase Enzyme) were confirmed to strongly interact with BrUFO protein. Discussion BrUFO gene should be a key gene of chinese cabbage against the infection of P. brassicae. BrUFO gene silencing improves the resistance of plants to clubroot disease. BrUFO protein may interact with CUS2 to induce ubiquitination in PRR-mediated PTI reaction through GDSL lipases, so as to achieve the effect of Chinese cabbage against the infection of P. brassicae.